1999
DOI: 10.1002/(sici)1097-0029(19990815/01)46:4/5<257::aid-jemt3>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Vipergic innervation of the mammalian pineal gland

Abstract: The present article reviews the literature relative to VIP- and PHI-containing nerve fibers in the pineal gland of mammals. The article summarizes data on the presence and distribution of the two peptides in the brain of mammals, their role in neuronal metabolism, and the significance and origin of VIPergic and PHIergic cerebrovascular nerve fibers. Special emphasis is placed on VIP- and PHI-containing nerves in the pineal gland. The morphology of the fibers, the nature of the innervation, and the distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…The pineal gland of all mammalian species studied so far contains a VIPergic innervation (see Cozzi, 1999 for review). The species studied include rabbit, cat and pig (Uddman et al, 1980), rat (Mikkelsen et al, 1987), gerbil Shiotani et al, 1986), sheep (Cozzi et al, 1990), and mouse .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The pineal gland of all mammalian species studied so far contains a VIPergic innervation (see Cozzi, 1999 for review). The species studied include rabbit, cat and pig (Uddman et al, 1980), rat (Mikkelsen et al, 1987), gerbil Shiotani et al, 1986), sheep (Cozzi et al, 1990), and mouse .…”
mentioning
confidence: 99%
“…Shiotani et al (1986) have demonstrated, in the gerbil, that the VIP fibers originate from the parasympathetic pterygopalatine ganglia. In addition, some VIP fibers may originate from central structures that project to the pineal gland or from the trigeminal ganglia (in the sheep, Cozzi, 1999). VIPergic fibers of parasympathetic origin enter the pineal gland through the pial capsule, travel within the gland following the blood vessels, and end among clusters of pinealocytes; central VIPergic fibers enter via the deep pineal gland.…”
mentioning
confidence: 99%